Evaluation Hospital Information System Implementation Using Technology Acceptance Model to Enhance Patient Satisfaction - Wati, Wiwin Sri Niscahya; Santoso, Budi; Cahyono, Dwi (Universitas Muhammadiyah Sorong, 2025)
This study examines the implementation of the Hospital Management Information System at Kaliwates General Hospital, with a focus on its impact on service efficiency and patient satisfaction. Using the Technology Acceptance Model, this research explores how Perceived Ease of Use, Perceived Usefulness, Trust, and Perceived Risk influence patient attitudes and behavioral intentions toward using the system. A quantitative approach was employed with Structural Equation Modeling to analyze the relationships among these variables and their effects on SIMRS adoption. A sample of 169 patients who interacted with SIMRS at Kaliwates Hospital participated in the study. The results indicate that PEOU and PU significantly influence both Attitude Toward Using and Behavioral Intention to Use. Trust plays a pivotal role in mitigating perceived risks and shaping positive attitudes toward the system, while Perceived Risk has a significant negative impact on patient attitudes. The findings further reveal the mediating role of these factors in influencing patients’ behavioral intentions to adopt the system. This study provides valuable insights into the factors influencing technology adoption in healthcare settings and offers actionable recommendations for improving SIMRS implementation, particularly by enhancing the user experience, ensuring robust data security, and providing continuous training and support for patients. Hospital Management Information System, Perceived Ease of Use, Perceived Risk, Perceived Usefulness, Trust, Technology Acceptance Model.